2016
DOI: 10.13189/eer.2016.040406
|View full text |Cite
|
Sign up to set email alerts
|

Assessing a Mercury Affected Area from Small-scale Gold Mining in Poboya, Central Sulawesi, Indonesia

Abstract: Poboya, Central Sulawesi is one of the primary sites used for small-scale gold mining activities in Indonesia. Poboya consumes 200-500 kg of mercury/day by amalgamation. Palu, the capital city of Central Sulawesi, is a city with a population of 0.35 million people and located around 11 km away from the edge of a small-scale gold mining area in Poboya. Fifteen samples of upper layer soil and fifteen samples of plant (Calotropis gigantean) were taken along the road that connects Poboya to Palu, at every 500 m. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Open Access 0.005 ppm (Mirdat et al, 2013;Sari et al, 2016). Mercury has also polluted the waters around the Poboya gold mine (Purnawan et al, 2013).…”
Section: Original Researchmentioning
confidence: 99%
“…Open Access 0.005 ppm (Mirdat et al, 2013;Sari et al, 2016). Mercury has also polluted the waters around the Poboya gold mine (Purnawan et al, 2013).…”
Section: Original Researchmentioning
confidence: 99%
“…Asian countries experiencing rapid industrialisation are confronted with considerable contamination of their agricultural soils. For example, large quantities of mercury from the chemical industry and gold mines are released into the environment (Sari et al, 2016). Arsenic is also naturally present in groundwater in many parts of Bangladesh and western India (Rahman, Dong and Naidu, 2015;Mojid et al, 2016).…”
Section: Trends In Developing Countriesmentioning
confidence: 99%
“…It is resulting in a decrease in the food supply in Palu City. Previous research in Poboya found a change in agricultural land's function into a gold mining area with a very high mercury pollution level and threatening Palu residents' health on a large scale [6,7].…”
Section: Introductionmentioning
confidence: 98%